Causality between various cytokines and asthma: a bidirectional two-sample Mendelian randomization analysis - Zheng, Yansen; Chen, Qi; Shi, Xiaqing; Lei, Lei; Wang, Donglin (Frontiers in Medicine, 2024)
Background Many studies have shown that cytokines play an important role in the pathogenesis of asthma, but their biological effects on asthma remain unclear. The Mendelian randomization (MR) method was used to evaluate the causal relationship between various cytokines [such as interleukins (ILs), interferons (IFNs), tumor necrosis factors (TNFs), colony-stimulating factors (CSFs), transforming growth factor (TGF), etc.,] and asthma. Methods In this study, inverse variance weighting was used to evaluate the causal relationship between asthma and cytokines. In addition, the reliability of the results is ensured by multiple methods such as MR-Egger, weighted median, MR-Raps, MR-Presso, and RadialMR, as well as sensitivity analysis. Results The results showed that none of the 11 cytokines was associated with the risk of asthma. In contrast, asthma can increase levels of IL-5 [odds ratio (OR) = 1.112, 95% confidence interval (CI): 1.009–1.224, P = 0.032] and IL-9 (OR = 1.111, 95% CI: 1.013–1.219, P = 0.025). Conclusion Genetically predicted asthma was positively associated with elevated levels of IL-5 and IL-9, indicating the downstream effects of IL-5 and IL-9 on asthma. Medical treatments can thus be designed to target IL-5 and IL-9 to prevent asthma exacerbations.